Double‐dorsal versus single‐volar digital subcutaneous anaesthetic injection for finger injuries in the emergency department: A randomised controlled trial. (16th March 2016) - Martin, Shane P; Chu, Kevin H; Mahmoud, Ibrahim; Greenslade, Jaimi H; Brown, Anthony FT
Abstract: Objective: The objective of this present study is to compare pain associated with the double‐dorsal versus a single‐volar subcutaneous injection in the provision of digital anaesthesia for finger injuries presenting to the ED. Methods: A randomised controlled trial from November 2012 to January 2014 at a single adult tertiary‐referral hospital. ED patients with finger injuries requiring digital anaesthesia was randomised to either the double‐dorsal or a single‐volar subcutaneous injection technique. The primary outcome was patient reported injection pain measured on a 100 mm visual analogue scale with the assessor blinded to the injection technique. The secondary outcome was success of anaesthesia defined as ability to perform the assessment and treatment without further anaesthetic supplementation after 5 min. Results: Eighty‐six patients were enrolled. Median (IQR) age was 34 (24–47) years and 79% were men. The majority (66.3%) had distal phalanx injuries. Forty patients were randomised to the double‐dorsal and 46 to a single‐volar subcutaneous injection technique. The mean (standard deviation) pain score of the double‐dorsal injection was 39.1 (24.2) and a single‐volar injection was 37.3 (24.5) with a difference of 1.8 (95% CI –8.8 to 12.3). Digital anaesthesia was successful in 64.9% of the double‐dorsal and 71.7% of the single‐volar subcutaneous injections, a difference of 6.8% (95% CI –12.7 to 26.3). Conclusion: In ED patients with finger injuries requiring digital anaesthesia, both the double‐dorsal or single‐volar subcutaneous injection techniques have similar pain of injection and success rates of anaesthesia. Single‐volar injection appears suitable alternative to the commonly performed double‐dorsal injection in the ED.